Controllable release of pirfenidone by polyvinyl alcohol film embedded soft contact lenses in vitro and in vivo. (1st January 2021) - Wu, Caiqing; Or, Ping Wai; Chong, Jones Iok Tong; K. Pathirage Don, Isuru K.; Lee, Ching Hymn Christopher; Wu, Kaili; Yu, Minbin; Lam, David C. C.; Yang, Yangfan
Abstract: To increase the amount of pirfenidone (PFD) loaded in polyvinyl alcohol (PVA) film embedded soft contact lens (SCL), and evaluate its function of sustaining delivery of drug in vitro and in vivo . Drug loading efficiency within PVA film and SCLs, drug release from SCLs in vitro, and the effects of parameters of SCLs and external environment on drug release in vitro were evaluated by ultraviolet–visible spectrophotometer at 312 nm. Safety of SCLs was evaluated in vitro by transformed human corneal epithelial cell. Safety in vivo was determined by optical coherence tomography and histology of anterior segment of rabbits. Drug release study in tear fluid and aqueous humor were measured by ultra-performance liquid chromatography. SCLs had smooth surface and were fit for experimental rabbits. Amount of PFD in PVA film and SCLs were 153.515 μg ± 12.508 and 127.438 μg ± 19.674, respectively, PFD in PVA film was significantly higher than SCLs ( p =.006) and closed to 150 μg (targeting amount of PFD to be loaded). Thickness of SCLs, molecular weight of PVA, and amount of PVA used in SCLs affected drug release in vitro significantly. Thickness of PVA film and amount of drug in SCLs had no effect on drug release rate in vitro . SCLs were safe in vitro and in vivo, PFD released from SCLs could be detected around 12 hours in tears and aqueous humor, and the concentration of drug was higher than eye drop at all detected time points while amount of PFD in SCLs was lower than eye drop. Drug loaded PVA film embedded SCLs may be a promising ocular drug delivery system.